2011
DOI: 10.3368/aoj.61.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Why do Children with Down Syndrome Have Subnormal Vision?

Abstract: People with Down syndrome have a wide variation in visual acuity, but generally 20 / 40 or worse. Both the eye and brain tend to be different in these patients compared to age matched normal subjects. Also, accommodative insufficiency (determined by dynamic retinoscopy) is often present in children Down syndrome, making bifocals a necessary consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 34 publications
0
19
0
2
Order By: Relevance
“…In literature, the following prevalences have been reported: reduced visual acuity (poorer than 0.3 LogMar) in 80–100% and poor contrast sensitivity in almost all DS children (John et al. ; Morton ; Little et al. ; Watt et al.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In literature, the following prevalences have been reported: reduced visual acuity (poorer than 0.3 LogMar) in 80–100% and poor contrast sensitivity in almost all DS children (John et al. ; Morton ; Little et al. ; Watt et al.…”
Section: Introductionmentioning
confidence: 99%
“…Their brain development differs from typically developing children. In particular, in children with DS less brain weight is found, there is dendritic atrophy, and poor maturation of the central nervous system has been described (Courage et al 1994;Little et al 2009a, Morton 2011Watt et al 2015). In recent years, research has shown that their visuospatial memory is better than their verbal memory (Lanfranchi et al 2004;Frenkel & Bourdin 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We were unable to assess the exact role of an amblyopic component in our patients, but there is a possibility that some of the patients did not attain good vision postoperatively due to amblyopia 28. It has also been suggested that individuals with Down's syndrome may have a wide variation in visual acuity due to differential characteristics between the eye and the brain29 and other associated neuropathologies 30. Also, as mentioned previously, it may be difficult to accurately assess the visual function and visual acuity in these patients due to subnormal mental intelligence.…”
Section: Discussionmentioning
confidence: 88%